Water management in membrane electrolysis and options for advanced plants. (23rd April 2019) - Müller, Martin; Carmo, Marcelo; Glüsen, Andreas; Hehemann, Michael; Saba, Sayed; Zwaygardt, Walter; Stolten, Detlef
Abstract: The development of polymer electrolyte membrane electrolysis (PEMEL) is driven by increasing performance to decrease the costs of electrolysis systems. One option for increasing power density is decreasing the Ohmic losses within the cell. This can be enabled by using thinner membranes, although the disadvantage of thin membranes is their lower diffusion resistivity for water, hydrogen and oxygen what influences the efficiency and the operating conditions. In this paper the water transport and the Ohmic resistance of catalyst coated membranes with different thickness are analyzed. The disadvantage of high water permeability in thin membranes can be used to change the feed configuration in stacks and systems. It is possible to feed the electrolysis only from the cathode, which simplifies the mass transport (single phase) in the anode's porous transport layer and reducing stack and system dimensions, as well as costs. Highlights: The diffusive water transport in Nafion membranes was electrochemically assessed. The performance of catalyst coated membranes was improved by reducing Ohmic resistance. An alternative and simplified electrolysis system design for hydrogen production is presented. The advanced system can be around 15% cheaper than systems with cathodic and anodic media supply.